Differential impact of two critical respiratory centers in opioid-induced respiratory depression in awake mice - Varga, Adrienn G. (J Physiol, 2019)
The primary cause of death from opioid overdose is respiratory failure. High doses of opioids cause severe rate depression and increased risk of fatal apnea, which correlate with increasing irregularities in breathing pattern. Mu opioid receptors (MORs) are widely distributed throughout the brainstem respiratory network, but the mechanisms underlying respiratory depression are poorly understood. The medullary pre-Bötzinger complex (preBötC) and the pontine Kölliker-Fuse nucleus (KF) are considered critical for inducing opioid-related respiratory disturbances. We used a conditional knockout approach to investigate the roles and relative contribution of MORs in KF and preBötC neurons in opioid-induced respiratory depression in awake adult mice. The results revealed dose-dependent and region-specific opioid effects on the control of both respiratory rate and pattern. Respiratory depression induced by an anti-nociceptive dose of morphine was significantly attenuated following deletion of MORs from either the KF or preBötC, suggesting cumulative network effects on respiratory rate control at low opioid doses. Deletion of MORs from KF neurons also relieved rate depression at near-maximal respiratory depressant doses of morphine. Meanwhile, deletion of MORs from the preBötC had no effect on rate following administration of high doses of morphine. Instead, a severe ataxic breathing pattern emerged with many apneas. We conclude that opioids affect distributed areas of the respiratory network and opioid-induced respiratory depression cannot be attributed to only one area in isolation. However, countering the effects of near maximal respiratory depressant doses of opioids in the KF may be a powerful approach to combat opioid overdose.